USING AUTHENTIC MATERIAL FROM MAGAZINES TO ENHANCE THE STUDENTS’ READING COMPREHENTION - Lailatul Nikmah; Anis Azimah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Although English has been taught in schools starting from kindergarten/elementary to junior high school levels, the fact shows that many student still difficult to read English texts. They may read fast but get nothing or they need a very long time to understand the texts. It means that they are not effective readers. It can be assumed that their comprehension skill is not good. Dealing with these phenomena, the teacher be given another authentic material from magazine to make their student to be effective readers. Because of that the teacher uses other material from magazine to solve the students’ problem. So we expect that this material helps students to deepen their reading comprehension and ability to apply this material.